The Golem and the Decline of Language and Magic—Or, Why Our Machines Disappoint. - Rosenberg, Joel. (Tufts University. Tisch Library., 2018)
Memories and Monsters explores the nature of the monstrous or uncanny, and the way psychological trauma relates to memory and narration. This interdisciplinary book works on the borderland between psychology and philosophy, drawing from scholars in both fields who have helped mould the bourgeoning field of relational psychoanalysis and phenomenological and existential psychology. The editors have sought out contributions to this field that speak to the pressing question: how are we to attend to and contend with our monsters? This is an Accepted Manuscript of a book chapter published by Routledge in Memories and Monsters: Psychology, Trauma, and Narrative, 2017, available online: http://www.routledge.com/9781138065451.